Synthesis of highly functionalized 2,2'-bipyridines by cyclocondensation of β-ketoenamides – scope and limitations - Hommes, Paul; Reissig, Hans-Ulrich (Beilstein Journal of Organic Chemistry, 2016)
The scope of a flexible route to unsymmetrically functionalized bipyridines is described. Starting from 1,3-diketones 1a–e, the corresponding β-ketoenamines 2a–e were converted into different β-ketoenamides 3a–g by N-acylation with 2-pyridinecarboxylic acid derivatives. These β-ketoenamides were treated with a mixture of TMSOTf and Hünig’s base to promote the cyclocondensation to 4-hydroxypyridine derivatives. Their immediate O-nonaflation employing nonafluorobutanesulfonyl fluoride provided the expected 4-nonafloxy-substituted bipyridine derivatives 5a–g in moderate to good overall yields. The bipyridyl nonaflates are excellent precursors for palladium-catalyzed reactions as demonstrated by representative Suzuki and Sonogashira couplings. Thus, a library of specifically substituted bipyridine derivatives was generated, showing the versatility of the simple 1,3-diketone-based approach to this important class of ligands.
Keywords: 2,2-bipyridines; cross couplings; cyclocondensation; β-ketoenamides; nonaflates